Odpowiedź:
a)
[tex]4*(-0,2)*(-0,25)=\\\\4*(-\frac{2}{10} )*(-\frac{1}{4} )=\\\\2*(-\frac{2}{5} )*(-\frac{1}{4} )=\\\\2*\frac{2}{20} =\frac{2}{10} =0,2[/tex]
b)
[tex]\frac{1}{2} *(-\frac{3}{4} )*8=\\\\\frac{1}{2} *(-3)*2=\\\\\frac{1}{2} * (-6)=-3[/tex]
c)
[tex](-8)*(1\frac{1}{3} )*\frac{5}{4} *(-0,1)=\\\\(-8)*(\frac{4}{3} )*\frac{5}{4} *(-0,1)=\\\\(-8)*\frac{5}{3} *(-0,1)=\\\\-\frac{40}{3} *(-\frac{1}{10} )=\frac{40}{30} =\frac{4}{3}[/tex]
d)
[tex]8*(-0,7)*(-\frac{1}{2} )*10=\\\\80*(-\frac{7}{10} )*(-\frac{1}{2} )=\\\\80*\frac{7}{20} =\\\\4*7=28[/tex]
e)
[tex]-5*\frac{2}{3} *(-1,5)*0,2=\\\\-5*\frac{2}{3} *(-\frac{15}{10} )*\frac{2}{10} =\\\\-5*(-\frac{5}{5} )*\frac{2}{10} =\\\\-5*(-1)*\frac{2}{10} =\\\\5*\frac{2}{10} =\frac{2}{2} =1[/tex]
f)
[tex]-\frac{3}{7} *\frac{5}{6} *(-4,9)*20=\\\\-\frac{15}{42} *(-\frac{49}{10} )*20=\\\\-\frac{15}{42} *(-\frac{49}{1} )*2=\\\\-\frac{15}{42} *(-98)=\\\\\frac{1470}{42} =35[/tex]